2020
DOI: 10.1101/2020.07.27.20162628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of hypertension and controlled hypertension among United States adults: Evidence from NHANES 2017-18 survey

Abstract: Background: This study aims to compare the prevalence of hypertension (HTN) and controlled hypertension (CHTN) in US adults and determine the absolute difference in the prevalence of HTN and CHTN between the JNC7 and ACC/AHA 2017 guidelines. Methods: Data for this study were derived from the most recent cycle of the National Health and Nutrition Examination Survey (NHANES) 2017-2018. After excluding participants with missing systolic blood pressure (BP) or diastolic BP and aged <18 years, 4730 participants… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The baseline MSAD rates seen in our cohort generally reflected those of the US population 21–24 . In the year following AIH diagnosis, nearly two‐thirds of patients had co‐morbid MSAD with one in six of AIH patients overall developing any form of de novo MSAD.…”
Section: Discussionmentioning
confidence: 58%
“…The baseline MSAD rates seen in our cohort generally reflected those of the US population 21–24 . In the year following AIH diagnosis, nearly two‐thirds of patients had co‐morbid MSAD with one in six of AIH patients overall developing any form of de novo MSAD.…”
Section: Discussionmentioning
confidence: 58%
“…Hypertension is the leading cause of cardiovascular disease and stroke 1 and poses a significant economic burden with estimated healthcare cost of $48.5 billion annually. 2 The definition of hypertension has evolved over the years. The American College of Cardiology and the American Heart Association (AHA) define hypertension as systolic blood pressure (SBP) ≥ 130 mm Hg and/or diastolic blood pressure (DBP) ≥ 80 mm Hg in their joint 2017 guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…4 The estimated prevalence of hypertension in the United States is 45.4% with more than half of the individuals having uncontrolled hypertension. 2 In the United States, studies have consistently demonstrated racial disparity in hypertension particularly among African American and Mexican-American individuals. 5 Immigrants and war refugees represent another vulnerable group [6][7][8] Exposure to humanitarian crises such as war, leads to worsening cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure definition for hypertension (>140/90 mm Hg) [ 1 ], in 2017-2018, 31.7% of US adults aged ≥18 years had hypertension, with a disproportionate impact on non-Hispanic Black adults (40.1%) compared with non-Hispanic White adults (32.7%) [ 2 ]. Hypertension is a leading contributor to cardiovascular disease burden; however, the underlying causes of essential hypertension, which accounts for 95% of all cases [ 3 ], are still ill-defined.…”
Section: Introductionmentioning
confidence: 99%